Analysis of the Value of Physical Activity to Children’s Mental Health Education in the Epidemic Era - Jingshu Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This research aims to examine the contribution of physical activity to children's mental health education during the epidemic era. In this study, 50 5- to 6-year-old children from a city were recruited as research subjects using interviews, literature review, and experimental statistics and then randomly divided into two groups: the experimental group and the control group. The psychological index data before and after the happy exercise were measured using a questionnaire survey. The psychological index data before and after 12 weeks of experimental practice were evaluated using data statistics. Six mental health indices demonstrated a significant difference between the experimental group and the control group, with the improvement value of the experimental group's movement score being 3.68 and the improvement value of the control group's movement score being 0.15. Social score improvement in the experimental group was 1.76, whereas, in the control group, it was 0.12. The value of language score improvement was 1.16, while the language score improvement in the control group was 0.14. The gymnastics sports curriculum is favorable to the mental health development of 56-year-old children and has significantly enhanced children's mental health.